Study and Analysis of Barriers for Implementation of Industry 4.0 Technologies Using Spherical Fuzzy TOPSIS Method - Akshay Kumar; Chimata Murli Krishna (SAGE Open)
The objective of this research work is to study and analyze the most influential barriers, and minimize their effect for successful implementation of industry 4.0 technologies in the manufacturing industry. The identified barriers are classified into (i) operational, (ii) technical, and (iii) social barriers. Drivers are proposed to minimize the effect of barriers, and a relationship between barriers and drivers has been established using data collected from a questionnaire survey for the manufacturing industry in India. A multicriteria decision-making (MCDM) model is formulated and is solved by using a proposed methodology involving interval-valued spherical fuzzy sets (IVSF) based TOPSIS method. The results indicate that high investment, communication between operational and information technologies, and the resistance of employees to change prove to be potential barriers for the manufacturing industry in developing countries. Drivers such as government initiatives, establishment of fast internet connectivity, job security, etc., are recommended in this research work for minimizing the effect of barriers.